Euphorbia species latex: A comprehensive review on phytochemistry and biological activities - Benjamaa, Rania; Moujanni, Abdelkarim; Kaushik, Neha; Choi, Eun Ha; Essamadi, Abdel Khalid; Kaushik, Nagendra Kumar (Frontiers in Plant Science, 2022)
The genus Euphorbia includes about 2000 species commonly widespread in both temperate and tropical zones that contain poisonous milky juice fluid or latex. Many species have been used in traditional and complementary medicine for the treatment of various health issues such as dropsy, paralysis, deafness, wounds, warts on the skin, and amaurosis. The medicinal applications of these species have been attributed to the presence of various compounds, and most studies on Euphorbia species have focused on their latex. In this review, we summarize the current state of knowledge on chemical composition and biological activities of the latex from various species of the genus Euphorbia. Our aim was to explore the applications of latex extracts in the medical field and to evaluate their ethnopharmacological potential. The bibliographic data indicate that terpenoids are the most common secondary metabolites in the latex. Furthermore, the latex has interesting biological properties and pharmacological functions, including antibacterial, antioxidant, free radical scavenger, cytotoxic, tumor, anti-inflammatory, healing, hemostatic, anti-angiogenic, insecticidal, genotoxic, and mutagenic activities. However, the role of other components in the latex, such as phenolic compounds, alkaloids, saponins, and flavonoids, remains unknown, which limits the application of the latex. Future studies are required to optimize the therapeutic use of latex extracts.